ALAT PENGHITUNG WAKTU DAN PENGONTROL BRIGHTNESS PADA MONITOR KOMPUTER - Mahardika Apriliandi, Aldy; Amanda Tia, Tariska; Ocsirendi, Ocsirendi; Yandi, Misri (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Computer monitors are a device that is widely used by all groups, both young and old. This rapid technological advancement can have both positive and negative impacts. The increasingly popular use of the internet can cause users to spend hours in front of computer monitors. Being in front of a computer monitor for too long can have an impact on the sense of sight, namely the eyes. In addition, the monitor screen emits x-rays that can interfere with eye health. Common problems caused by excessive users include the effects of radiation, headaches, insomnia, reproductive disorders, cancer, leukemia, tumors, and other personal health problems. In addition, excessive use of computer monitors can also lead to mild physical fatigue, recurrent headaches, ear disorders, depression, heart attacks, skin cancer, sexual dysfunction, low blood pressure, and body imbalances. Experts suggest that the maximum time to use this computer monitor is 1-2 hours per day, and the need to maintain a safe viewing while using a computer monitor is about 40-50 centimeters from the screen. By keeping the eye away from the screen, the exposure to light received by the eye from the screen can be reduced. To minimize the impact of eye health from exposure to the use of computer monitors, based on the description above, the author took the title of the Final Project, namely